The Cause and Trend of Contraceptive Discontinuation in India: A Comprehensive Analysis Employing a Multiple Decrement Model - Tiwari, Abhay Kumar; Saroj, Chitra (Brazilian Journal of Biometrics, 2025)
The usage of contraceptives and family planning are hot issues of conversation due to the growing population. Here authors have done a comprehensive study on contraceptive discontinuation in India. This article describes the trend in contraceptive discontinuation in India and the multiple decrement concept is used to determine the probability of contraceptive discontinuation in India. Data used in this research were taken from the country’s National Family and Health Survey. The contraceptive discontinuation trend reveals that from NFHS 1 to NFHS 5 there is a decline of 15.25% in contraceptive discontinuation in India. It was realized that in NFHS 1, the highest discontinuation was due to fertility-related causes, and in NFHS 5, it was due to method-related causes. The age groups where the highest discontinuation occurred were 40-49 and 25-29 in NFHS 1 and NFHS 5, respectively.